2021
DOI: 10.1037/pspi0000305
|View full text |Cite
|
Sign up to set email alerts
|

A matter of flexibility: Changing outgroup attitudes through messages with negations.

Abstract: Attitudes toward outgroups are an important determinant of peaceful coexistence in diverse societies, but it is difficult to improve them. The current research studies the impact of messages with negations on outgroup attitudes, more specifically on outgroup trust. All studies were preregistered. Using different target groups, Studies 1 and 2 provide evidence for the prediction that communicating negations (e.g., “they are not deceptive”) enhances outgroup trust (more so than affirmations, such as “they are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 98 publications
(172 reference statements)
3
47
0
Order By: Relevance
“…Across six experiments, we investigated whether cognitive conflicts caused by messages with negations (e.g., "Asylum seekers are not lazy") reduces the impact of dominant outgroup attitudes on outgroup judgements and whether an increase in cognitive flexibility would explain this effect (Winter et al, 2021a). In general, processing negations (e.g., "the door is not closed") requires a two-step mental simulation of conflicting alternatives (Kaup et al, 2007).…”
Section: Cognitive Conflicts Reduce the Impact Of Dominant Outgroup Attitudesmentioning
confidence: 99%
“…Across six experiments, we investigated whether cognitive conflicts caused by messages with negations (e.g., "Asylum seekers are not lazy") reduces the impact of dominant outgroup attitudes on outgroup judgements and whether an increase in cognitive flexibility would explain this effect (Winter et al, 2021a). In general, processing negations (e.g., "the door is not closed") requires a two-step mental simulation of conflicting alternatives (Kaup et al, 2007).…”
Section: Cognitive Conflicts Reduce the Impact Of Dominant Outgroup Attitudesmentioning
confidence: 99%
“…Thus, the results in principle support the idea that an increase in cognitive flexibility (here due to high ingroup diversity) would lead to a reconsideration of previously held beliefs, that is, mitigate defaults in group-based trust. This ties in with a growing body of research that shows debiasing effects of increased cognitive flexibility in intergroup relations (e.g., Sassenberg & Moskowitz, 2005;Vasiljevic & Crisp, 2013;Winter et al, 2021). On the other hand, the observed effect is too small in size to be considered meaningful for practical purposes.…”
Section: Discussionmentioning
confidence: 69%
“…In line with this, Foddy and colleagues (2009) found that interaction partners from a positively stereotyped outgroup (i.e., nursing students) were preferred (i.e., trusted more) over members of a negatively stereotyped outgroup (i.e., economics students) in a monetary allocation game. Irrespective of the (positive or negative) outgroup Winter, K., & Sassenberg, K. (2021). Mitigating the Default?…”
Section: Defaults In Group-based Trustmentioning
confidence: 99%
See 2 more Smart Citations